ARTERIAL STIFFNESS DETERMINED BY CARDIO-ANKLE VASCULAR INDEX IN PATIENTS WITH FAMILIAL HYPERCHOLESTEROLEMIA - Khomkamon, Nitchada (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Measurement of arterial stiffness is recommended for enhancing cardiovascular risk stratification, especially in high CV risk patients with familial hypercholesterolemia (FH). Therefore, early detection of arterial stiffness in FH patients with no established atherosclerotic cardiovascular disease is a rationale strategy. Cardio-ankle vascular index (CAVI) is generally used as a tool to measure arterial stiffness. However, there are few studies about arterial stiffness measurement in patients with FH. This study aims to compare arterial stiffness between patients with dyslipidemia with and without FH. METHODOLOGY A cross-sectional study was performed between 2019 to 2021 in Phramongkutklao Hospital. Patients with dyslipidemia were recruited. The Dutch Lipid Clinic Network (DLCN) criteria was used for the diagnosis and classification of participants with FH and control (non-FH). Arterial stiffness was determined by CAVI in all participants. A correlation between CAVI and hypercholesterolemia was performed. Factors associated with abnormal arterial stiffness (CAVI >8.0) were determined. RESULTS All 55 participants completed the study. Baseline characteristics were comparable between the FH and non-FH groups, except for mean low-density lipoproteincholesterol (220.1 ± 45.6 and 147.85 ± 50.1, respectively) (p <0.001). Based on DLCN criteria, there were no definite cases, 5 (9.09%) probable, 21 (38.18%) possible, 26 (47.28%) unlikely and 3 (5.45%) as others. Mean ± SD of CAVI in FH and control groups were 7.5 ± 1.7, and 7.3 ± 1.8, respectively (p = 0.819). The correlation between LDL-cholesterol level and CAVI was also not significant (r = 0.24, p = 0.12). Factors associated with abnormal arterial stiffness were age and hypertension. CONCLUSION Arterial stiffness, determined by CAVI was not found to enhance CV risk in patients with possible or probable FH in this study. Factors associated with abnormal arterial stiffness were age and hypertension.